How do I break down (x-2)/((x+1)(x-1)^2) into partial fractions?

Firstly, let (x-2)/((x+1)(x-1)2) = A/(x+1) + B/(x-1)+C/(x-1)2, where A,B and C are to be calculated. 

Then, multiply both sides of the equation by (x+1)(x-1)2 which will leave an equation as follows;

x-2 = A(x-1)2 + B(x+1)(x-1) +C(x+1). Now let x=1.

-1 = 0A + 0B + 2C   this implies C = -1/2

Now let x = -1

-3 = A*(-2)2  + 0B + 0C  this implies -3=4*A which means A = -3/4

Now we have equation: x-2 = (-3/4)(x-1)2  + B(x-1)(x+1)  -(1/2)(x+1)

If we let x = 0 we get; 

-2 = -3/4 -B  - 1/2 giving; 

-2 = -5/4 - B          Adding 5/4 to both sides gives  -3/4 = - B from which we can see B = 3/4

now we have transformed our initial fraction into partial fractions; 

(x-2)/((x+1)(x-1)2) = -3/4(x+1) + 3/4(x-1)  -1/2(x-1)2 

To check your answers enter in an arbitrary x, both sides should come to the same number. 

Answered by Daniel O. Maths tutor

3347 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Use the double angle formulae and the identity cos(A+B)≡cos(A)cos(B)−sin(A)sin(B) to obtain an expression for cos 3x in terms of cos x only


Express 9^(3x+)1 in the form 3^y giving y in the form of ax+b where a and b are constants.


How do I find the angle between 2 vectors?


A curve is defined for x>0 as y = 9 - 6x^2 - 12x^4 . a) Find dy/dx. b) Hence find the coordinates of any stationary points on the curve and classify them.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences